Effect of antimicrobials, salinity, and contamination by air on bacterial and fungal growth in cyprid cultures of Amphibalanus improvisus. (19th February 2019) - Ochi Agostini, Vanessa; Macedo, Alexandre José; Muxagata, Erik
Abstract: Barnacles are crustaceans of ecological and economic importance. Larvae of barnacles such as Amphibalanus improvisus are cultivated in laboratories in order to study their biology and ecology. However, the culturing of invertebrates promotes the growth of microorganisms, which can eventually kill the invertebrates. The use of antimicrobials combined with aseptic techniques can inhibit the growth of bacteria and fungi. The objective of this study was to evaluate the effect of antimicrobials on bacterioplankton and mycoplankton growth in cyprid cultures of A. improvisus at different salinities, with or without air exposure. For this, we evaluated the survival and settlement of A. improvisus cyprids and free‐living and biofilm bacterial inhibition in an antimicrobial medium exposed to different salinities (1, 15, and 25) and under uncovered and covered (PVC film) cultures. With the data obtained, we observed the absence of negative effects on the survival and settlement of A. improvisus and determined the antimicrobial treatment efficacy (using a combination of 0.025 g/L of penicillin G potassium, 0.08 g/L of streptomycin sulfate, 0.04 g/L of neomycin sulfate, and 0.005 g/L of nystatin) in inhibiting free‐living and biofilm microorganisms (bacteria and fungi). This treatment could be used to inhibit bacterial and fungal growth in marine cultures with a salinity above 25. The effectiveness of the treatment is considerably enhanced by covering the cultures to reduce contamination by air.